VALUES OF MEAN CORPUSCULAR HEMOGLOBIN CONCENTRATION, MEAN CORPUSCULAR VOLUME AND MEAN CORPUSCULAR HEMOGLOBIN IN BALI CATTLE BASED ON ORGANIC MAINTAIN - Adinata, I Gede Agus Eva Prawira; Suwiti, Ni Ketut; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2021)
Research has been done to find out the hematological value of MCHC (Mean Corpuscular Hemoglobin Concentration), MCV (Mean Corpuscular Volume), and MCH (Mean Corpuscular Haemoglobin) of Bali cattle with organic-based maintenance. An organic-based maintenance system is the management of feeding that comes from the environment and does not use pesticides or other chemicals. The method used by checking the value of MCV, MCH, and MCHC bali cattle blood is measured using a Veterinary hematology analyzer. The result showed that the value of MCHC was 39,71%dl, the value of MCV was 44,48 fl, and the MCH’s value was 18,69pg. It can be concluded that the average value is still within the normal range based on the index value of cattle’s erythrocytes in general.